The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/aln.0b013e3181ac461f
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular Approach Is an Easy and Safe Method of Subclavian Vein Catheterization Even in Mechanically Ventilated Patients

Abstract: Subclavian venous catheterization via the supraclavicular approach is an excellent method of central venous access in mechanically ventilated patients. The procedure success rate and the significant complication rate are comparable to other techniques of central venous catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
0
23
0
3
Order By: Relevance
“…This method can be used successfully and relatively safely by inexperienced as well as experienced physician as a primary or alternative technique when other catheterization sites are not available. 6 Success of cannulation in our study revealed, in Group S 95%, where as in Group I was 92.5% which was statistically not significant with p value of >0.05. This was consistent with study done by Durrani et al 4 where the overall success rate was 96.4% in supraclavicular group and 91.1% in infraclavicular group.…”
Section: Discussionmentioning
confidence: 79%
“…This method can be used successfully and relatively safely by inexperienced as well as experienced physician as a primary or alternative technique when other catheterization sites are not available. 6 Success of cannulation in our study revealed, in Group S 95%, where as in Group I was 92.5% which was statistically not significant with p value of >0.05. This was consistent with study done by Durrani et al 4 where the overall success rate was 96.4% in supraclavicular group and 91.1% in infraclavicular group.…”
Section: Discussionmentioning
confidence: 79%
“…Using the deltoid tuberosity approach, the cutaneous puncture site is placed 1.5 cm inferior to the medial border of this landmark, and the needle is advanced toward the sternoclavicular joint and sternal notch 44. Other landmarks described include the coraco-clavicular line45 and the deltopectoral triangle 46,39…”
Section: Subclavian Cannulationmentioning
confidence: 99%
“…It can augment the spectrum of catheterization possibilities, even in mechanically ventilated patients. [13] It is also an easy cannulation technique for the inexperienced physician and a useful alternative to traditional approaches for the experienced physician. [8]…”
Section: Discussionmentioning
confidence: 99%